Anatomi Penipuan Digital dan Tantangan Penegakan Hukumnya di Indonesia: Dari Social Engineering hingga Deepfake, serta Problematika Rezim Pembuktian - Gilang Rizki Aji Putra (BULETIN ADALAH, 2023)
Abstract: Digital fraud has become the most pervasive criminal modality in the digital economy, transcending territorial boundaries and systematically exploiting human psychological vulnerabilities. This article analyzes the anatomy and evolving modus operandi of digital fraud in Indonesia and identifies the multidimensional challenges in its enforcement. Using normative legal research with case, statutory, and comparative approaches, the study finds that digital fraud has evolved from conventional phishing into complex psychological manipulation schemes enhanced by deepfake technology and automated systems. The analysis reveals that Indonesia’s criminal law framework, including the Penal Code and the Electronic Information and Transactions Law, still contains fundamental weaknesses in jurisdiction, evidentiary standards, and digital asset tracing. Major cases, such as binary options scams and banking social engineering schemes, confirm that law enforcement agencies often struggle to match the speed and sophistication of offenders. The article concludes that effective enforcement requires jurisdictional reform, strengthened digital forensic capacity, and enhanced international cooperation mechanisms. Keywords: Digital Fraud, Social Engineering, Deepfake, Electronic Information and Transactions Law (ITE Law), Digital Evidence